Development of the “Highly Sensitive Dog” questionnaire to evaluate the personality dimension “Sensory Processing Sensitivity” in dogs - Braem, Maya; Asher, Lucy; Furrer, Sibylle; Lechner, Isabel; Würbel, Hanno; Melotti, Luca (PLOS ONE, 2017)
In humans, the personality dimension ‘sensory processing sensitivity (SPS)’, also referred to as “high sensitivity”, involves deeper processing of sensory information, which can be associated with physiological and behavioral overarousal. However, it has not been studied up to now whether this dimension also exists in other species. SPS can influence how people perceive the environment and how this affects them, thus a similar dimension in animals would be highly relevant with respect to animal welfare. We therefore explored whether SPS translates to dogs, one of the primary model species in personality research. A 32-item questionnaire to assess the “highly sensitive dog score” (HSD-s) was developed based on the “highly sensitive person” (HSP) questionnaire. A large-scale, international online survey was conducted, including the HSD questionnaire, as well as questions on fearfulness, neuroticism, “demographic” (e.g. dog sex, age, weight; age at adoption, etc.) and “human” factors (e.g. owner age, sex, profession, communication style, etc.), and the HSP questionnaire. Data were analyzed using linear mixed effect models with forward stepwise selection to test prediction of HSD-s by the above-mentioned factors, with country of residence and dog breed treated as random effects. A total of 3647 questionnaires were fully completed. HSD-, fearfulness, neuroticism and HSP-scores showed good internal consistencies, and HSD-s only moderately correlated with fearfulness and neuroticism scores, paralleling previous findings in humans. Intra- (N = 447) and inter-rater (N = 120) reliabilities were good. Demographic and human factors, including HSP score, explained only a small amount of the variance of HSD-s. A PCA analysis identified three subtraits of SPS, comparable to human findings. Overall, the measured personality dimension in dogs showed good internal consistency, partial independence from fearfulness and neuroticism, and good intra- and inter-rater reliability, indicating good construct validity of the HSD questionnaire. Human and demographic factors only marginally affected the HSD-s suggesting that, as hypothesized for human SPS, a genetic basis may underlie this dimension within the dog species.